Flood detection system / Airulhafzan Johari - Johari, Airulhafzan (2004)
The flood will become too much strain to the affected persons. Today's, many floods occur not only in the rural area but also include the urban area which has a good manage drain facilities. We cannot predict the situation but we can take pre caution action on risk of life and reduce the properties destruction. Just bear in mind it will happen anytime, anyplace without counter to any other else. We need some time to prepare before the flood occurs. What can be done to at least reduce the negative impacts of floods? One system must be built to inform the affection person about the situation. So this system has been build to solve the problem that haunted them with a cheap and easy way to encounter this situation. Flood detection system is the system that being used to detect the rising water level in the river. When the water rises, circuit will send signal to the system. The system will inform the rising of water level to the several departments that in charge the disaster using email or sms. The main purpose of flood detection system is to avert or minimize loss of life. We expanded this vision and defined the purpose of the flood detection system as a means of establishing public safety, to reduce damage to property and to relieve public anxiety